Energy-efficient data-gathering rendezvous algorithms with mobile sinks for wireless sensor networks. (2017) - Zhang, Jian; Tang, Jian; Wang, Tianbao; Chen, Fei
Energy conservation or energy balance in the process of data gathering has always been a crucial issue for prolonging the lifetime of wireless sensor networks (WSNs), especially on the premise of the introduction of mobile elements to cope with the phenomenon of hot spots or energy holes. In this paper, we propose optimal cluster-based mechanisms by a modified multi-hop layered model for load balancing with multiple mobile sinks for these problems. Furthermore, under the condition of a delay-tolerant application, rendezvous points (RPs) and rendezvous nodes (RNs) are utilised to realise the goal of optimal/suboptimal energy consumption in the sense of energy transmission model through a heuristic algorithm in a geometrical way. To further reduce the consumption of network energy, quantisation technologies are exploited. As a result, we analyse the cluster lifetimes in different situations and achieve balance to save significant energy.